2021
DOI: 10.1016/j.ajogmf.2021.100459
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating mental health education in obstetrics and gynecology: a call to action

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Additional educational objectives not explicitly covered in guidance from national professional bodies Some studies identified additional educational objectives, not covered in guidance from national professional bodies. These included teaching on intimate partner violence, 31 content for Muslim patients, 27 mental health education, 32 and training requirements in low-and middle-income countries. Key differences identified by our rapid review were requirements for students to be skillful enough to perform insertion of intrauterine contraceptive devices, repair episiotomies, and perform cervical biopsies, endometrial biopsies, and colposcopy.…”
Section: Obstetrics and Gynecology Curriculum Content For Medical Stu...mentioning
confidence: 99%
“…Additional educational objectives not explicitly covered in guidance from national professional bodies Some studies identified additional educational objectives, not covered in guidance from national professional bodies. These included teaching on intimate partner violence, 31 content for Muslim patients, 27 mental health education, 32 and training requirements in low-and middle-income countries. Key differences identified by our rapid review were requirements for students to be skillful enough to perform insertion of intrauterine contraceptive devices, repair episiotomies, and perform cervical biopsies, endometrial biopsies, and colposcopy.…”
Section: Obstetrics and Gynecology Curriculum Content For Medical Stu...mentioning
confidence: 99%
“…In a recent call to action on the importance of cultivating mental health in obstetrics and gynecology, creators of the NCRP revealed the plan to develop a curriculum oriented toward obstetric trainees that will be modeled after the NCRP. 50 The consistent gaps in education on perinatal mental health across both psychiatric and obstetric training programs highlight that there may be untapped opportunities for collaborative learning across specialties. This could also foster open sharing of resources and help develop cooperative care networks and research infrastructure.…”
Section: Ongoing Areas Of Innovationmentioning
confidence: 99%
“…In a recent call to action on the importance of cultivating mental health in obstetrics and gynecology, creators of the NCRP revealed the plan to develop a curriculum oriented toward obstetric trainees that will be modeled after the NCRP. 50 The consistent gaps in education on perinatal mental health across both psychiatric and obstetric training programs highlight that there may be…”
Section: Ongoing Areas Of Innovation Educationmentioning
confidence: 99%
“…The authors recognize further work needs to be done to enhance education during obstetrics and gynecology residency programs for the future generation of providers. 83 This work is also likely needed for advanced practice providers, family medicine residents, psychiatry residents, psychology interns, and social work trainees. For current practicing providers, there are several avenues to improve current knowledge around perinatal mental health.…”
Section: Resourcesmentioning
confidence: 99%